3D laser metal printing in zero gravity using additive manufacturing - Akhtar, Shariq (Cranfield University, 2019)
Poster presented at Cranfield University's 2019 Manufacturing Doctoral Community event.
Keywords: 3D Printing; space manufacturing; laser deposition; MDC19 poster; Additive Manufacturing